You replace the p in the given expression by -2 and the m by 3 and simplify
So its (-2)^ / 4 - 3
= 4/4 - 3
= 1 - 3 (note the division 4/4 is done first according to the order of operations rule)
= -2 answer
Answer:
8y8
i recomend you to use p.h.o.t.o.m.a.t.h
Answer:
24
Step-by-step explanation:
════════ ∘◦❁◦∘ ════════
<h3>Final value : x² -9x - 11</h3>
════════════════════
<h3>Step by step </h3>
![\frac{1}{(x - 2)} + \frac{1}{(x + 3)} = \frac{1}{5}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B%28x%20-%202%29%7D%20%20%2B%20%20%5Cfrac%7B1%7D%7B%28x%20%2B%203%29%7D%20%20%3D%20%20%20%5Cfrac%7B1%7D%7B5%7D%20)
![\frac{(x + 3) + (x - 2)}{(x - 2)(x + 3)} = \frac{1}{5}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%28x%20%2B%203%29%20%2B%20%28x%20-%202%29%7D%7B%28x%20-%202%29%28x%20%2B%203%29%7D%20%20%3D%20%20%5Cfrac%7B1%7D%7B5%7D%20)
![\frac{2x + 1}{ {x}^{2} + 3x - 2x - 6 } = \frac{1}{5}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2x%20%2B%201%7D%7B%20%7Bx%7D%5E%7B2%7D%20%2B%203x%20-%202x%20-%206%20%7D%20%20%3D%20%20%5Cfrac%7B1%7D%7B5%7D%20)
![\frac{2x + 1}{ {x}^{2} + x - 6} = \frac{1}{5}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2x%20%2B%201%7D%7B%20%7Bx%7D%5E%7B2%7D%20%20%2B%20x%20-%206%7D%20%20%3D%20%20%5Cfrac%7B1%7D%7B5%7D%20)
2x + 1 = ⅕ × (x² + x - 6)
2x + 1 = ⅕x² + ⅕x - 6/5
1/5x² +1/5x - 2x - 6/5 - 1 = 0
1/5x² -9/5x - 11/5 = 0
x² - 9x - 11 = 0. #times by 5
════════════════════
#Give me brainliest pls im tired typing all of this